Development of Textbooks on Animal Embryology and Reproduction Based on Research Results in the Development of Mice Embryos by Adding DEET (Diethyltoluamide) - Kusmawati, Wiwik; Iza, Nikmatul; Hindun, Nurmala; Nuh, Fuad Azhar (Universitas Malikussaleh, 2019)
The purpose of this study was to develop a textbook on Embryology and Animal Reproduction based on the research on the development of mouse embryos by adding DEET (Diethyltoluamide) that was appropriate and validated by material, media and language experts. This research is a development study of textbooks on animal embryology and reproduction based on the results of research on the development of mouse embryos by adding DEET. The development of this textbook refers to the 4D model developed by Thiagarajan, et al. (1974) which consisted of 4 stages, namely Define, Design, Development, and Disseminate, which were modified to be adapted to this study. This development research produced a textbook on Embryology and Animal Reproduction based on research on the development of mouse embryos by adding proper DEET and validating it by material, media and language experts.